Design and Programming Atmega Microcontroller - Denny Irawan; Rini Puji Astutik (Kontribusia : Research Dissemination for Community Development, 2020)
Along with the demands for improving the quality of education, teacher competencies must be able to face the challenges of changes that occur in society. Professional competence in Law No. 14 of 2005 requires that teachers be competent in the learning process. More specifically, technical skills teachers are required to be able to transfer knowledge, attitudes, and skills in vocational expertise to students. Therefore, improving the quality of learning coupled with an increase in mastery of the substance of learning becomes an important and fundamental thing that must be mastered by the teacher in order to strengthen the mastery of expertise competencies.With regard to competency certification in dealing with the Asean economic framework (AEC) that has been launched in 2016, students who graduate from Vocational High Schools must have certification about certain skills. In this case, the University of Muhammadiyah Gresik University as a university which also has an obligation to conduct community education plans to conduct training on making Atmega microcontroller modules for SMK Manbaul Ulum Gresik students.